#TITLE_ALTERNATIVE# - FAJAR SAPUTRI , DWI
This final project studies the run-up and inundation (local name 'rob') caused by tides in an extreme condition (perigee and spring tide) in the northern coast of Jakarta on 24-27 November 2007. The run-up and inundation has been simulated using a two-dimensional (2D) hydrodynamic model with Flooding and Drying (FAD) fasilities. Tidal elevation data derived from the Tidal Model Driver (TMD) were used at the open boundaries. Bathymetric data were obtained from GEBCO, map of Jan-Hidros TNI-AL and topograhic of the Northern Jakarta was obtained form Digital Elevation Model (DEM) derived from SRTM. Simulation results incdicate that the most affected inundation areas are Kecamatan Penjaringan, Kecamatan Pademangan, Kecamatan Tanjung Priok, dan Kecamatan Cilincing which are the same areas observed in the field. The maximum inundation height is in Muara Baru on November 26 at 11.00 am which reaches 0.62 m height and the maximum inundation distance is in Kecamatan Pademangan that reaches 6.1 km on November 27 at 13.00 am.